The effect of the electric field on the nucleation of the nanometer periodic structure of adatoms in GaAs semiconductor under the action of laser irradiation - Peleshchak, R.M.; Kuzyk, O.V.; Dan'kiv, O.O.; Guba, S.K. (Condensed Matter Physics, 2019)
In the paper, the effect of the electric field on the conditions of formation and on the period of the surface superlattice of adatoms in n-GaAs semiconductor is investigated. It is established that in GaAs semiconductor, an increase in the electric field strength, depending on the direction, leads to an increase or decrease of the critical temperature (the critical concentration of adatoms), at which the formation of self-organized nanostructure is possible. It is shown that in strongly alloyed n-GaAs semiconductor, an increase of the electric field strength leads to a monotonous change (decrease or increase depending У роботi дослiджено вплив електричного поля на умови формування та перiод поверхневої надгратки адсорбованих атомiв у напiвпровiднику n-GaAs. Встановлено, що у напiвпровiднику GaAs збiльшення напруженостi електричного поля залежно вiд напрямку призводить до збiльшення або зменшення критичної температури (критичної концентрацiї адатомiв), при якiй можливе формування самоорганiзованої наноструктури. Показано, що у сильнолегованому напiвпровiднику n-GaAs збiльшення напруженостi електричного поля призводить до монотонної змiни (зменшення чи збiльшення залежно вiд напрямку електричного поля) перiоду самоорганiзованих поверхневих наноструктур адатомiв.